PENINGKATAN KETERAMPILAN KOLABORATIF MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN BERDIFERENSIASI MAPEL MATEMATIKA - Novianto, Aditya; Wardani, Krisma Widi (Universitas Negeri Medan, 2025)
Students' collaborative skills can be improved by applying the Problem based learning model and differentiation learning in mathematics subjects. This study is entitled Improving Collaborative Skills Using the Problem based learning Model in Differentiated Learning of Mathematics Subjects for Grade IV Students of SD Negeri Mlilir 01. This type of research is Classroom Action Research (CAR) using the Kemmis & MC Taggart model which is carried out in two cycles. In each cycle there are four stages, namely planning, action, observation and reflection. Based on the results of the study in cycle I, it shows that the results of group discussions obtained a percentage of 76.44% and the results of group attitude observations obtained 76.90%. Thus, the results of collaboration skills in cycle I obtained a percentage of 76.67%. In cycle II, the results of group discussions obtained a percentage of 84.42% and the results of group attitude observations obtained 80.98%. Thus, the results of collaboration skills in cycle II obtained a percentage of 82.70%. From these data, it can be seen that there was an increase in the percentage of collaboration skills from 76.67% to 82.70%. This proves that the researcher has succeeded in achieving the established collaboration skills indicator of 80%.